Samarium molybdate / reduced graphene oxide electro-catalytic material, preparation method and application thereof, and electrochemical sensor
By hydrothermal samarium molybdate/redox graphene electrocatalytic material and modifying glass carbon electrodes, electrochemical sensors are solved, which is difficult to achieve rapid, simple, sensitive and green environmental protection in the prior art detection of FZD, and achieves efficient and portable detection effects.
Patent Information
- Application Number
- CN202510071627.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to detect carcinogenic residue furazolidone (FZD) quickly, easily, sensitively and environmentally friendly. The traditional methods have insufficient equipment and time-consuming and labor-intensive operation.
Samarium molybdate/redox graphene electrocatalytic material was synthesized by hydrothermal synthesis, and modified on a glass carbon electrode to construct an electrochemical sensor for detection of FZD.
It realizes simple, efficient, green and environmentally friendly, responsive and portable FZD detection, and provides a new method for detecting carcinogenic residues.
Smart Images

Figure CN119873892A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic materials and electrochemical sensors, and in particular to a samarium molybdate / redox graphene electrocatalytic material, a preparation method and application thereof, and an electrochemical sensor. Background Art
[0002] An important aspect of nanotechnology is the combination of analytical tools to build new devices that break the manpower, expensive equipment, and time-consuming processes. In the field of materials science, technological innovations have fundamentally shaped chemical sensors with unique cutting-edge properties and used them as excellent complementary analytical tools. Moreover, in environmental analysis, continuous mass measurements are becoming more and more common to replace inferential quantification. Moreover, in the field of electrochemistry, the miniaturization, portability, and disposable nature of electrodes are increasingly attracting the interest of researchers as they provide significant convenience without compromising their potential.
[0003] The synthesis method and morphology of nanomaterials play a crucial role in the electrocatalytic activity of abundant materials. In order to prepare nanoparticles with a pure crystalline phase, a simple hydrothermal method is used, which is as effective as a solution reaction-based technique. The advantages of this method are uniform precipitation, low cost, increased vapor pressure, easy scale-up, and specific size and shape. Rare earth metal molybdates have made important contributions to the development of lasers, memory devices, infrared sensors, micro-armor, and fluorescent screens due to their unique physicochemical properties. In addition, the incorporation of semiconductor materials on carbon materials can promote catalytic active sites and prevent agglomeration. The development of simple and effective synthesis techniques has made SmM, which has unique physicochemical properties and is modified on the surface of graphene oxide, a potential candidate material in the field of electrocatalysis.
[0004] Researchers have explored the use of nanomaterials for surface modification of bare electrodes because nanomaterials have a large specific surface area, which greatly increases the casting of preferred elements on the electrode and promotes rapid electron transport, thereby improving the conductivity of the modified electrode. These properties are important requirements for sensors based on nanoparticles. Compared with other traditional technologies, the advantages of electrochemical sensors include low cost, mass production, low sample consumption, fast response, portability, adjustable design, simplicity, etc. Therefore, the development of new electrochemical sensors is a hot topic for researchers because it is easy to prepare for direct use in field detection.
[0005] Furazolidone ([N-(5-nitro-2-furan-3-amino)-2-oxazolidinone], FZD) is a synthetic nitrofuran antimicrobial drug widely used in veterinary medicine to treat bacterial infections in livestock and aquaculture. It is also widely used as a feed additive for food animals, including pigs, formed fish, shrimp and cattle. FZD is widely used as a growth promoter in food animals; however, it may lead to serious antibiotic residues through the food chain and cause side effects on human health. In addition, the presence of FZD residues in the food chain poses a huge health risk, leading to serious consequences such as leukopenia, skin inflammation, gastric spasm and cell growth inhibition, accompanied by the potential risks of hepatotoxicity, mutagenicity, carcinogenic activity and teratogenicity, and can also damage human DNA and hinder cell growth. Therefore, due to these harmful effects, FZD has been banned in many countries, including China, the European Union and the United States. Despite this, its illegal use in livestock, poultry and aquaculture still exists, resulting in residues in meat, eggs, honey and milk, thus posing a major threat to human health through the food chain. Therefore, it is very important to design a fast, simple, low detection limit, high sensitivity and environmentally friendly FZD analysis and detection method. Many analytical methods are used to detect furazolidone, such as chromatography, ultraviolet, capillary electrophoresis, immunoassay, and fluorescence to detect harmful residues. However, although these methods are widely used, they also have some shortcomings, such as expensive instruments, time-consuming and labor-intensive operations, and the need for professionally trained personnel to operate. Electrochemical sensors are simple, portable, fast-responding, and environmentally friendly. Therefore, it is of great significance to develop a sensitive, economical, and fast electrochemical sensor for the analysis of furazolidone and establish its accurate quantitative analysis method. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a samarium molybdate / redox graphene electrocatalytic material and a preparation method and application thereof, and an electrochemical sensor.
[0007] In a first aspect, the present invention provides a method for preparing a samarium molybdate / redox graphene electrocatalytic material, the preparation method comprising the following steps:
[0008] Dispersing GO in water and stirring to obtain a GO suspension;
[0009] Sm(NO3)3·6H2O and Na2MoO4·2H2O are added into water separately for ultrasonic dissolution, and then mixed to obtain a first mixed material;
[0010] Stirring and mixing the GO suspension and the first mixed material to obtain a second mixed material;
[0011] adding urea to the second mixed material, stirring and mixing, to obtain a third mixed material;
[0012] The third mixed material is heated for reaction, and then cooled, centrifuged, washed and dried to obtain the samarium molybdate / redox graphene electrocatalytic material.
[0013] Furthermore, based on every 0.1 mM of the Sm(NO3)3·6H2O, the amount of GO added is 20-25 mg, and the amount of urea added is 1-2 g; the molar ratio of the Sm(NO3)3·6H2O to the Na2MoO4·2H2O is 1:(1-2).
[0014] Furthermore, the working condition parameters of the heating reaction include: temperature of 170-190° C. and time of 12-16 hours.
[0015] Furthermore, the preparation method of GO comprises the following process:
[0016] Place 2-3g of graphite powder in a round-bottom flask, add 50-60mL of 98% concentrated H2SO4 by weight and stir for 20-30min, add 7-8g of KMnO4 in an ice-water bath and continue stirring for 1-2h to obtain a dark green solution; then place the flask in a 35-45℃ constant temperature water bath and stir for 2-3h to obtain a brown solution; after the reaction, add 50-60mL of distilled water to the mixed solution, transfer it to a 95-98℃ constant temperature water bath and stir for 20-30min, then take it out and add 50-60mL of distilled water; after high temperature reaction, slowly add 2-3mL of 30% H2O2 solution by weight, the color of the mixed solution turns to bright yellow and bubbles are generated; wash with 5% by weight dilute hydrochloric acid and secondary deionized water respectively to remove H + and SO 2- , until the pH of the solution is neutral, and finally freeze-dried for 24 to 48 hours to obtain the dry GO.
[0017] In a second aspect, the present invention provides a samarium molybdate / redox graphene electrocatalytic material, wherein the samarium molybdate / redox graphene electrocatalytic material is prepared by the preparation method described in any one of the first aspects.
[0018] In a third aspect, the present invention provides the use of the samarium molybdate / redox graphene electrocatalytic material described in any one of the second aspects in the preparation of an electrochemical sensor and in the detection of furazolidone.
[0019] In a fourth aspect, the present invention provides an electrochemical sensor, comprising a glassy carbon electrode and a detection material attached to the glassy carbon electrode, wherein the detection material is the samarium molybdate / redox graphene electrocatalytic material as described in any one of the second aspects.
[0020] Furthermore, the preparation method of the electrochemical sensor comprises the following steps:
[0021] The glassy carbon electrode is first cleaned, then polished, second cleaned and dried to obtain a first glassy carbon electrode;
[0022] Electrochemically activating the first glassy carbon electrode to obtain a second glassy carbon electrode;
[0023] The samarium molybdate / redox graphene electrocatalytic material is dissolved in a solvent, then dripped onto the second glassy carbon electrode and dried to obtain the electrochemical sensor.
[0024] In a fifth aspect, the present invention provides a method for detecting furazolidone using the electrochemical sensor according to any one of the fourth aspects, the method comprising the following steps:
[0025] The electrodes of the electrochemical sensor were placed in a solution containing 5 mM [Fe(CN)6] 3- / 4- The 0.05M PBS characterization solution was used to detect using cyclic voltammetry (CV) in the range of -0.2V to 0.6V and the electrochemical impedance spectroscopy (EIS) was used to measure its resistance;
[0026] The electrode of the sensor was placed in 0.05 M PBS containing 100 μM furazolidone, and cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were used for quantitative detection in the range of -0.6 V to -0.1 V and -0.8 V to 0 V, respectively.
[0027] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:
[0028] The embodiment of the present invention provides a samarium molybdate / redox graphene electrocatalytic material and its preparation method and application, and an electrochemical sensor. The present invention synthesizes the samarium molybdate / redox graphene electrocatalytic material by hydrothermal synthesis, and modifies the glassy carbon electrode to achieve the first application in electrochemical detection of FZD. Compared with traditional detection methods, the detection method of the present invention has the advantages of being simple and efficient, green and environmentally friendly, sensitive to response, and portable, and it provides a new way to detect carcinogenic residues. Specifically:
[0029] 1) By doping rare earth molybdate (Sm2(MoO4)3) into a carbon-based material (RGO) to prepare a composite material modified glassy carbon electrode, transition metal oxides cooperate with carbon materials to promote catalytic active sites, showing better electrocatalytic ability and stability, so as to obtain obvious and stable response signals, improve the repeatability and reproducibility of the sensor, and at the same time improve the sensitivity of detection.
[0030] 2) There are very few reports on the synthesis of this electrocatalytic material. This study used a hydrothermal synthesis method to synthesize the composite material, and electrochemical methods can be used within a certain voltage range to characterize part of the sensor's construction process.
[0031] 3) All the materials involved can be synthesized under laboratory conditions, which are easy to operate, the raw materials are cheap, low in toxicity, green and environmentally friendly, and the amount used each time is extremely small, which reduces the experimental cost.
[0032] 4) The electrochemical sensor prepared by this method can provide a new method for FZD detection; the electrochemical sensor prepared by this invention can also be used for the detection of other environmental pollutants and carcinogenic residues. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0035] Figure 1 A schematic flow chart of a method for preparing a samarium molybdate / redox graphene electrocatalytic material provided in an embodiment of the present invention.
[0036] Figure 2 This is the scanning electron microscope image of RGO;
[0037] Figure 3 This is the scanning electron microscope image of the SmM material;
[0038] Figure 4 Infrared spectra of RGO and SmM materials;
[0039] Figure 5 is the Raman spectrum of RGO;
[0040] Figure 6 Each modified electrode was placed in 5 mM K3[Fe(CN)6] / K4[Fe(CN)6] solution for CV characterization;
[0041] Figure 7 Each modified electrode was placed in 5 mM K3[Fe(CN)6] / K4[Fe(CN)6] solution for EIS characterization;
[0042] Figure 8Comparison of CV graphs of bare electrode and modified electrode detecting 100 μM furazolidone in 0.05 M PBS (pH = 7.0);
[0043] Fig. 9 Comparison of DPV diagrams of bare electrode and modified electrode detecting 100 μM furazolidone in 0.05 M PBS (pH=7.0). DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0046] In a first aspect, the present invention provides a method for preparing a samarium molybdate / redox graphene electrocatalytic material, such as Figure 1 As shown, the preparation method comprises the following steps:
[0047] Dispersing GO in water and stirring to obtain a GO suspension;
[0048] Sm(NO3)3·6H2O and Na2MoO4·2H2O are added into water separately for ultrasonic dissolution, and then mixed to obtain a first mixed material;
[0049] Stirring and mixing the GO suspension and the first mixed material to obtain a second mixed material;
[0050] adding urea to the second mixed material, stirring and mixing, to obtain a third mixed material;
[0051] The third mixed material is heated for reaction, and then cooled, centrifuged, washed and dried to obtain the samarium molybdate / redox graphene electrocatalytic material.
[0052] The embodiment of the present invention provides a method for preparing a samarium molybdate / redox graphene electrocatalytic material. The present invention synthesizes the samarium molybdate / redox graphene electrocatalytic material by a hydrothermal synthesis method, and modifies the glassy carbon electrode with the samarium molybdate / redox graphene electrocatalytic material to achieve the first application in electrochemical detection of FZD. Compared with traditional detection methods, the detection method of the present invention has the advantages of being simple and efficient, green and environmentally friendly, sensitive to response, and portable, and provides a new way to detect carcinogenic residues. Specifically:
[0053] The present invention prepares samarium molybdate (Sm2(MoO4)3) modified redox graphene (RGO) hybrid nanocomposite materials. The preparation methods of GOs include Brodie method, Staudenmaier method and Hummers method. The Hummers method is currently the most commonly used method for preparing GOs from graphite. Its advantages are that the strong oxidant KMnO4 is used to replace KCIO3 in the Brodie method to complete the reaction in a short time and avoid the problem of explosive ClO2 that may be generated by using chlorate; NaNO3 is used to replace HNO3 used in the Staudenmaier method to eliminate acid mist. However, the Hummers method still has disadvantages: (1) due to the introduction of NaNO3, toxic gases such as NO2 and N2O4 are formed; (2) the waste liquid generated during the GO synthesis process contains soluble ions Na that are difficult to separate. + and NO3 - , making it difficult to harmlessly treat the waste liquid. Studies have found that NaNO3 plays a role in assisting the intercalation of concentrated H2SO4 during the oxidation process of graphite, but at higher dosages of oxidant and intercalant, the effect of NaNO3 is not obvious. By changing the oxidation time to 0.5h, 1h, and 1.5h, it was found that the C / O atomic ratio of GOs decreased due to the continued oxidation reaction. At the same time, in the researchers' study of the preparation mechanism of GO, it was found that sodium nitrate only has an obvious auxiliary effect in the intercalation stage, but in the entire oxidation process of graphite, the amount of potassium permanganate and the oxidation reaction time play a decisive role. Therefore, we use the improved Hummers method to synthesize graphene oxide, that is, the synthesis reaction is carried out without adding sodium nitrate on the original basis.
[0054] Graphene is a flat 2D carbon nanomaterial with sp 2Hybridized carbon atoms, which are filled in the form of a honeycomb lattice. The discovery of graphene has unlocked innovations in the field of nanoscience and nanotechnology, and it is considered to be the thinnest material in the world today with no band gap, which makes it an excellent candidate for environmental applications. It has attracted great interest from researchers due to its excellent electrical conductivity, good mechanical properties, and large specific surface area. Among carbon-based nanomaterials, graphene (nanoscale) has shown good application prospects in various fields due to its excellent electrochemical and physical properties, and has attracted great attention due to its outstanding environmental applications. Transition metal oxides have been widely used in the field of electrochemical sensing due to their interesting electronic properties and structural composition, as well as their advantages such as low toxicity, stable structure, large effective specific surface area, high sensitivity, large adsorption capacity, and fast response time. The disadvantages of single metal oxides, such as easy deactivation and adverse effects of strong pH, ultimately led to the popularity of binary metal oxides, which have excellent electrochemical properties and remarkable environmental performance. In recent years, rare earth molybdates (RExMoyOz, RE=La, Ce, Nd, Pr, Sm, Dy, etc.) have gained greater interest due to their novel structural features and special properties (i.e., abnormal thermal expansion behavior, fast oxidized ion conduction, catalytic and luminescent properties), supercapacitors, lithium-ion energy-saving batteries, luminescent materials, electrochemical sensors and phosphors. Molybdates have excellent mechanical strength, fast oxidized ion conductivity and good structural stability, thermal stability and chemical stability, and have high application potential in laser photonics, optical signals, photoluminescence, scintillators and microwave applications. Double metal oxides of rare earth metals (R) and transition metals (T) are superior to double transition metal oxides (TT). Sm is a lanthanide metal and also belongs to rare earth metals. Due to its large interlayer spacing, special magneto-optical phenomenon and partially filled f electrons, it is conducive to the improvement of electrochemical performance, thereby showing efficient electrocatalytic performance. Because carbon materials are often used as carriers of metals to improve the sensitivity of electrochemical sensors, the synergistic effect of nanomaterials presents better advantages. Since molybdate has low conductivity, samarium molybdate (Sm2(MoO4)3) is used to modify RGO to form a nanocomposite material. The synergistic effect can improve the efficiency and stability of electron transfer and have better electrocatalytic ability. The modified electrode prepared by adding rare earth molybdate into the carbon-based material promotes comfortable charge transfer between the electrode and the electrolyte and improves the rate performance of the electrode. Therefore, the present invention reports a synthesis method of a hybrid nanocomposite material modified with redox graphene (RGO) by samarium molybdate (Sm2(MoO4)3), and uses the composite material to modify the electrode to detect the carcinogenic residue furazolidone (FZD), providing a new method for the detection of carcinogenic residues.
[0055] In some specific embodiments, based on every 0.1 mM of the Sm(NO3)3·6H2O, the amount of GO added is 20-25 mg, and the amount of urea added is 1-2 g; the molar ratio of the Sm(NO3)3·6H2O to the Na2MoO4·2H2O is 1:(1-2).
[0056] In some specific embodiments, the working condition parameters of the heating reaction include: temperature of 170-190° C. and time of 12-16 hours.
[0057] In some specific embodiments, the method for preparing GO comprises the following process:
[0058] Place 2-3g of graphite powder in a round-bottom flask, add 50-60mL of 98% concentrated H2SO4 by weight and stir for 20-30min, add 7-8g of KMnO4 in an ice-water bath and continue stirring for 1-2h to obtain a dark green solution; then place the flask in a 35-45℃ constant temperature water bath and stir for 2-3h to obtain a brown solution; after the reaction, add 50-60mL of distilled water to the mixed solution, transfer it to a 95-98℃ constant temperature water bath and stir for 20-30min, then take it out and add 50-60mL of distilled water; after high temperature reaction, slowly add 2-3mL of 30% H2O2 solution by weight, the color of the mixed solution turns to bright yellow and bubbles are generated; wash with 5% by weight dilute hydrochloric acid and secondary deionized water respectively to remove H + and SO 2- , until the pH of the solution is neutral, and finally freeze-dried for 24 to 48 hours to obtain the dry GO.
[0059] In some specific embodiments, the preparation method of the Sm2(MoO4)3 / RGO composite material (i.e., samarium molybdate / redox graphene electrocatalytic material) is as follows: weigh GO and disperse it in ultrapure water and stir it magnetically to obtain a uniform suspension. Then weigh Sm(NO3)3·6H2O and dissolve it ultrasonically in ultrapure water, weigh Na2MoO4·2H2O and dissolve it ultrasonically in ultrapure water (the molar ratio of the two is 1:1 to 1:2), and after both are completely dissolved to form a uniform solution, mix the two to obtain a white precipitate, ultrasonicate for 0.5h to 1h, mix the GO suspension with the above mixture, stir overnight, add 1 to 2g of urea, continue magnetic stirring for 0.5h to 1h, and then transfer the above solution to a high-temperature reactor and continue to react in an oven at 160℃ to 200℃ for 12 to 15h. After the reaction is completed, cool it to room temperature, centrifuge the mixture at 6000 to 8000rpm, and centrifuge and wash it several times with ultrapure water and anhydrous ethanol respectively. Finally, the obtained product is placed in a vacuum drying oven at 60°C to 80°C and dried for 10 to 12 hours.
[0060] In a second aspect, the present invention provides a samarium molybdate / redox graphene electrocatalytic material, wherein the samarium molybdate / redox graphene electrocatalytic material is prepared by the preparation method described in any one of the first aspects.
[0061] In a third aspect, the present invention provides the use of the samarium molybdate / redox graphene electrocatalytic material described in any one of the second aspects in the preparation of an electrochemical sensor and in the detection of furazolidone.
[0062] In a fourth aspect, the present invention provides an electrochemical sensor, comprising a glassy carbon electrode and a detection material attached to the glassy carbon electrode, wherein the detection material is the samarium molybdate / redox graphene electrocatalytic material as described in any one of the second aspects.
[0063] In some specific embodiments, the method for preparing the electrochemical sensor comprises the following steps:
[0064] The glassy carbon electrode is first cleaned, then polished, second cleaned and dried to obtain a first glassy carbon electrode;
[0065] Electrochemically activating the first glassy carbon electrode to obtain a second glassy carbon electrode;
[0066] The samarium molybdate / redox graphene electrocatalytic material is dissolved in a solvent, then dripped onto the second glassy carbon electrode and dried to obtain the electrochemical sensor.
[0067] In some specific embodiments, the method for preparing the electrochemical sensor comprises the following steps:
[0068] 1) Prepare FZD mother solution with DMF and store in a refrigerator at 4°C for later use;
[0069] 2) Soak the glassy carbon electrode in piranha solution (98% H2SO4 / 30% H2O2=3:1, v / v) for 6 hours and then rinse with ultrapure water for later use;
[0070] 3) The electrode obtained in step 2) was polished with 1 μm, 0.3 μm and 0.05 μm Al2O3 polishing powder to form a mirror surface, and then the electrode was ultrasonically cleaned in the order of ultrapure water, anhydrous ethanol and ultrapure water, and dried naturally for later use;
[0071] 4) electrochemically activating the electrode obtained in step 3) in 0.5M H2SO4, scanning several cycles by cyclic voltammetry to obtain a stable CV graph, then rinsing with ultrapure water and drying naturally;
[0072] 5) dropping the Sm2(MoO4)3 / RGO composite material solution onto the surface of the cleaned glassy carbon electrode in step 4) and drying at room temperature to obtain an electrochemical sensor for FZD detection.
[0073] In a fifth aspect, the present invention provides a method for detecting furazolidone using the electrochemical sensor according to any one of the fourth aspects, the method comprising the following steps:
[0074] The electrodes of the electrochemical sensor were placed in a solution containing 5 mM [Fe(CN)6] 3- / 4- The 0.05M PBS characterization solution was used to detect using cyclic voltammetry (CV) in the range of -0.2V to 0.6V and the electrochemical impedance spectroscopy (EIS) was used to measure its resistance;
[0075] The electrode of the sensor was placed in 0.05 M PBS containing 100 μM furazolidone, and cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were used for quantitative detection in the range of -0.6 V to -0.1 V and -0.8 V to 0 V, respectively.
[0076] The present invention prepares a transition metal molybdate (Sm2(MoO4)3) supported redox graphene (RGO) modified glassy carbon electrode for detecting carcinogenic residue furazolidone (FZD). In terms of material selection, rare earth metal molybdate (RE-MoS) has the advantages of high carrier mobility, narrow band gap, good electrochemical activity, etc., and is considered to be one of the most suitable catalysts for electrochemical sensors. Among the many RE-MOs catalysts, samarium molybdate (SmM) nanomaterials have received special attention in many fields such as photocatalysis, photoluminescence, electronics and magnetism due to their unique physicochemical properties. SmM nanomaterials can effectively transfer excitation energy to rare earth ions through charge due to their large absorption cross-section, stability and multivalence. In addition, the incorporation of semiconductor materials into carbon materials can promote catalytic active sites and prevent agglomeration. The present invention adopts Sm2(MoO4)3 and GO to form a composite material (Sm2(MoO4)3 / RGO), which significantly improves the signal response and signal stability of a single rare earth molybdate (Sm2(MoO4)3) or RGO, realizes signal amplification and thus improves the sensitivity of the sensor. In addition, in this work, a Sm2(MoO4)3 / RGO composite material is synthesized by a hydrothermal synthesis method using rare earth molybdate (Sm2(MoO4)3) and GO, and is used to modify a glassy carbon electrode. There are very few reports on the synthesis of the composite material. By the above means, the prepared electrochemical sensor is successfully used for the sensitive detection of FZD in environmental samples and biological samples. Compared with the traditional FZD detection method, the advantages of the present invention are high sensitivity, rapid detection, easy operation, low price of equipment and materials, and no pollution, thereby providing a new analytical method for the detection of FZD.
[0077] It should be noted that the raw material components involved in the samarium molybdate / redox graphene electrocatalytic material and its application provided in the embodiments of the present invention, unless otherwise specified or described, can be directly purchased from the market or made in-house according to existing preparation methods; at the same time, the operating steps involved in the preparation method, unless otherwise specified or described, can be carried out according to existing liquid silicone material preparation methods.
[0078] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0079] The main chemical reagents used in the embodiments of the present invention are as follows:
[0080] Furazolidone (FZD) was purchased from MacLean Biotechnology Co., Ltd. (Shanghai, China); samarium nitrate hexahydrate (Sm(NO3)3·6H2O) was purchased from MacLean Biotechnology Co., Ltd. (Shanghai, China); graphite powder and sodium molybdate dihydrate (Na2MoO4·2H2O) were purchased from Aladdin Biochemical Technology Co., Ltd. (Shanghai, China); urea was purchased from Chongqing Chuandong Chemical.
[0081] Equipment and technical parameters used:
[0082] Instrumentation: Differential pulse voltammetry (DPV), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS) were performed using a Shanghai Chenhua electrochemical workstation (CHI660D, Shanghai, China). Electrochemical detection used a three-electrode system: a modified glassy carbon electrode (4 mm in diameter) was used as the working electrode, a platinum wire was used as the counter electrode, and a saturated calomel electrode (SCE) was used as the reference electrode. Electrochemical three-electrode system DPV was performed in 0.05 M PBS solution (pH 7.0) with a voltage range of −0.8 V to 0 V (vs. SCE), and CV was scanned at 100 mV / s in 5 mM K3[Fe(CN)6] / K4[Fe(CN)6] solution with a voltage range of −0.6 V to 0.2 V (vs. SCE). A pH meter was used to monitor pH (S210 Seven Compact, Mettler-Toledo, Shanghai, China). 1 / 100000 balance (SQP, Sartorius, Beijing, China); high-speed refrigerated centrifuge (H2-16KR, Hunan, China).
[0083] Example 1
[0084] The preparation of the electrochemical sensor for detecting the carcinogenic residue furazolidone (FZD) of the present invention is carried out according to the following steps:
[0085] (1) Preparation of materials;
[0086] 1) The preparation method of Sm2(MoO4)3 is as follows: weigh 0.1mM Sm(NO3)3·6H2O and ultrasonically dissolve it in ultrapure water, weigh 0.2mM NaMoO4·2H2O and ultrasonically dissolve it in ultrapure water, and after both are completely dissolved to form a uniform solution, mix the two to obtain a white precipitate, ultrasonicate for 1 hour, and magnetically stir overnight, then add 1.25g urea, continue stirring for 0.5h, and then transfer the mixture to a high-temperature reactor to react at 180℃ for 14h. After the reaction is completed, cool it to room temperature, centrifuge the mixture at 6000rpm, and wash it several times with ultrapure water and anhydrous ethanol. Finally, place the obtained product in a vacuum drying oven at 60℃ and dry it for 10h to obtain Sm2(MoO4)3 material;
[0087] 2) The improved preparation method based on the Hummers method is as follows: Place 2g of graphite powder (5000 mesh) in a round-bottom flask, add 50mL of 98% concentrated H2SO4 and stir for 20min, add 7.5g of KMnO4 in an ice water bath and continue stirring for 1h to obtain a dark green solution. Secondly, place the flask in a 45℃ constant temperature water bath and stir for 2h to obtain a brown solution. After the reaction, add 50mL of distilled water to the mixed solution, transfer it to a 95℃ constant temperature water bath and stir for 30min, then take it out and add another 50mL of distilled water. After the high temperature reaction, slowly add 3mL of 30% H2O2 solution, and the color of the mixed solution turns bright yellow (bubbles are generated). Wash it with 5% dilute hydrochloric acid and secondary deionized water several times to remove H in the solution. + and SO 2- , until the pH of the solution was neutral, and finally freeze-dried for 24 h to obtain dry GO.
[0088] 3) The preparation method of Sm2(MoO4)3 / RGO composite material is as follows: weigh 22 mg GO and disperse it in ultrapure water and stir it magnetically to obtain a uniform suspension. Then weigh 0.1 mM Sm(NO3)3·6H2O and dissolve it in ultrapure water by ultrasonication, and weigh 0.2 mM Na2MoO4·2H2O and dissolve it in ultrapure water by ultrasonication. After both are completely dissolved to form a uniform solution, mix the two to obtain a white precipitate, ultrasonicate for 1 hour, mix the GO suspension with the above mixture, stir overnight, add 1.25 g urea, continue magnetic stirring for 0.5 hour, then transfer the above solution to a high-temperature reactor and continue to react in an oven at 180°C for 14 hours. After the reaction is completed, cool it to room temperature, centrifuge the mixture at 6000 rpm, and wash it several times with ultrapure water and anhydrous ethanol respectively. Finally, place the obtained product in a vacuum drying oven at 60°C and dry it for 10 hours;
[0089] The synthesized material was characterized by scanning electron microscopy using Example 1 to obtain SEM images of RGO and SmM materials. Figure 2 and Figure 3 As shown;
[0090] The synthesized material was characterized by Fourier infrared spectroscopy using Example 1 to obtain FT-IR images of RGO and SmM materials, as shown in FIG. Figure 4 As shown;
[0091] The synthesized RGO material was characterized by Raman spectroscopy using Example 1 to obtain the Raman spectrum of RGO. Figure 5 As shown;
[0092] The preparation method of RGO is as follows: weigh GO and disperse it in 10mL ultrapure water, stir it magnetically overnight, then add urea with a GO / urea (mass ratio) of 1:50 to the dispersion, stir it for 0.5 to 1h, then transfer the mixed system to a 25mL reactor containing polytetrafluoroethylene, and heat it to 180°C in an oven for 10 to 14h, cool it to room temperature after the reaction, centrifuge the mixture at 6000 to 8000rpm, and wash it several times with ultrapure water and anhydrous ethanol. Finally, dry the obtained product in a vacuum drying oven at 40°C to 60°C for 10 to 12h.
[0093] The preparation method of Sm2(MoO4)3 (abbreviated as SmM) is as follows: weigh Sm(NO3)3·6H2O and dissolve it in ultrapure water by ultrasonic, weigh Na2MoO4·2H2O and dissolve it in ultrapure water by ultrasonic (the molar ratio of the two is 1:1-1:2), after both are completely dissolved to form a uniform solution, mix the two to obtain a white precipitate, ultrasonicate for 0.5h-1h, stir magnetically overnight, add 1-2g urea, continue stirring for 0.5h-1h, then transfer the mixture to a high-temperature reactor and continue to react in an oven at 160℃-200℃ for 12-15h, cool to room temperature after the reaction, centrifuge the mixture at 6000-8000rpm, and wash the mixture several times with ultrapure water and anhydrous ethanol. Finally, the obtained product is placed in a vacuum drying oven at 60℃-80℃ and dried for 10-12h to obtain Sm2(MoO4)3 material.
[0094] (2) Construction of electrochemical sensor for FZD detection:
[0095] 1) Prepare FZD mother solution with DMF and store in a refrigerator at 4°C for later use;
[0096] 2) Soak the glassy carbon electrode in piranha solution (98% H2SO4 / 30% H2O2=3:1, v / v) for 6 hours and then rinse with ultrapure water for later use;
[0097] 3) The electrode obtained in step 2) was polished with 1 μm, 0.3 μm and 0.05 μm Al2O3 polishing powder to form a mirror surface, and then the electrode was ultrasonically cleaned in the order of ultrapure water, anhydrous ethanol and ultrapure water, and dried naturally for later use;
[0098] 4) electrochemically activating the electrode obtained in step 3) in 0.5M H2SO4, scanning several cycles by cyclic voltammetry to obtain a stable CV graph, then rinsing with ultrapure water and drying naturally;
[0099] 5) Weigh 3 mg of the composite material and disperse it in 1 mL of ultrapure water, and ultrasonicate for 30 min to obtain a uniformly dispersed suspension, and prepare GCE and Sm2(MoO4)3 / RGO / GCE modified electrodes for use.
[0100] 6) 8 μL of the Sm2(MoO4)3 / RGO composite material solution was dropped onto the clean glassy carbon electrode surface obtained in step 4) and dried at room temperature to obtain an electrochemical sensor for FZD detection.
[0101] Example 2
[0102] Detection of furazolidone FZD using electrochemical sensor
[0103] The electrochemical sensor constructed in Example 1 was used to detect FZD, and the following steps were followed:
[0104] 1) The modified electrodes from step (4) to step 6) of Example 1 were placed in 5 mM K3[Fe(CN)6] / K4[Fe(CN)6] solution for CV and EIS characterization. The current response signals were measured. The results are as follows: Figure 6 and Figure 7 As shown;
[0105] 2) 8 μL of the material was added to the modified electrode prepared in Example 1, and the CV and DPV current responses of 100 μM target FZD in 0.05 M PBS (pH = 7.0) were measured. Figure 8 and Fig. 9 shown.
[0106] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0107] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A method for preparing a samarium molybdate / redox graphene electrocatalytic material, characterized in that: The preparation method comprises the following steps: Dispersing GO in water and stirring to obtain a GO suspension; Sm(NO3)3·6H2O and Na2MoO4·2H2O are added into water separately for ultrasonic dissolution, and then mixed to obtain a first mixed material; Stirring and mixing the GO suspension and the first mixed material to obtain a second mixed material; adding urea to the second mixed material, stirring and mixing, to obtain a third mixed material; The third mixed material is heated for reaction, and then cooled, centrifuged, washed and dried to obtain the samarium molybdate / redox graphene electrocatalytic material.
2. The method for preparing the samarium molybdate / redox graphene electrocatalytic material according to claim 1, characterized in that: Based on every 0.1 mM of the Sm(NO3)3·6H2O, the amount of GO added is 20-25 mg, and the amount of urea added is 1-2 g; the molar ratio of the Sm(NO3)3·6H2O to the Na2MoO4·2H2O is 1:(1-2).
3. The method for preparing the samarium molybdate / redox graphene electrocatalytic material according to claim 1, characterized in that: The working condition parameters of the heating reaction include: temperature of 170-190° C. and time of 12-16 hours.
4. The method for preparing the samarium molybdate / redox graphene electrocatalytic material according to claim 1, characterized in that: Preparation method of GO The process includes: Place 2-3 g of graphite powder in a round-bottom flask, add 50-60 mL of 98% concentrated H2SO4 by weight and stir for 20-30 min, add 7-8 g of KMnO4 in an ice-water bath and continue stirring for 1-2 h to obtain a dark green solution; then place the flask in a 35-45°C constant temperature water bath and stir for 2-3 h to obtain a brown solution; after the reaction, add 50-60 mL of distilled water to the mixed solution, transfer it to a 95-98°C constant temperature water bath and stir for 20-30 min, then take it out and add 50-60 mL of distilled water; after high temperature reaction, slowly add 2-3 mL of 30% H2O2 solution by weight, the color of the mixed solution changes to bright yellow and bubbles are generated; wash with 5% by weight dilute hydrochloric acid and secondary deionized water respectively to remove H + and SO 2- , until the pH of the solution is neutral, and finally freeze-dried for 24 to 48 hours to obtain the dry GO.
5. A samarium molybdate / redox graphene electrocatalytic material, characterized in that: The samarium molybdate / redox graphene electrocatalytic material is prepared by the preparation method of the samarium molybdate / redox graphene electrocatalytic material according to any one of claims 1 to 4.
6. Use of the samarium molybdate / redox graphene electrocatalytic material according to claim 5 in preparing an electrochemical sensor and detecting furazolidone.
7. An electrochemical sensor, characterized in that The electrochemical sensor comprises a glassy carbon electrode and a detection material attached to the glassy carbon electrode, wherein the detection material is the samarium molybdate / redox graphene electrocatalytic material according to claim 5.
8. The electrochemical sensor according to claim 7, characterized in that The preparation method of the electrochemical sensor comprises the following steps: The glassy carbon electrode is first cleaned, then polished, second cleaned and dried to obtain a first glassy carbon electrode; Electrochemically activating the first glassy carbon electrode to obtain a second glassy carbon electrode; The samarium molybdate / redox graphene electrocatalytic material is dissolved in a solvent, then dripped onto the second glassy carbon electrode and dried to obtain the electrochemical sensor.
9. A method for detecting furazolidone using the electrochemical sensor according to claim 7 or 8, characterized in that: The method comprises the following steps: The electrodes of the electrochemical sensor were placed in a solution containing 5 mM [Fe(CN)6] 3- / 4- The resistance of the samples was measured in the range of -0.2V to 0.6V using cyclic voltammetry and 0.05M PBS characterization solution using AC impedance technology. The electrodes of the sensor were placed in 0.05 M PBS containing 100 μM furazolidone, and cyclic voltammetry and differential pulse voltammetry were used for quantitative detection in the range of -0.6 V to -0.1 V and -0.8 V to 0 V, respectively.
Citation Information
Cited By
Synthesis of samarium molybdate / functionalized multi-walled carbon nanotube-based composite material and application of samarium molybdate / functionalized multi-walled carbon nanotube-based composite material to detection of antibacterial drug dimethyl-nidazole
CN117929506A